2014
DOI: 10.3892/ijmm.2014.1799
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized high-density lipoprotein impairs the function of human renal proximal tubule epithelial cells through CD36

Abstract: Abstract. Unlike native high-density lipoprotein (HDL), oxidized HDL exerts adverse effects in a number of diseases, including chronic kidney disease (CKD); however, the mechanisms involved in this process remain unclear. In the present study, we investigated the effects of oxidized HDL on renal tubular cells, which play an important role in the progression of CKD. Human renal proximal tubule epithelial cells (HK-2) were cultured and stimulated with various concentrations of oxidized HDL in the absence or pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The main MAPKs are P38, ERK1/2 and c-Jun N-terminal kinase 1/2, whose activity is stimulated by phosphorylation. The ROS-induced activation of MAPKs has been reported in several kidney diseases (26)(27)(28), while the association between UA and MAPKs has largely remained elusive; however, previous studies have indicated the participation of MAPKs in UA-induced tubular cell apoptosis (29,30). As the underlying mechanisms required further elucidation, the present study examined the phosphorylation of P38 and ERK1/2 and found them significantly activated following exposure to UA.…”
Section: Discussionmentioning
confidence: 94%
“…The main MAPKs are P38, ERK1/2 and c-Jun N-terminal kinase 1/2, whose activity is stimulated by phosphorylation. The ROS-induced activation of MAPKs has been reported in several kidney diseases (26)(27)(28), while the association between UA and MAPKs has largely remained elusive; however, previous studies have indicated the participation of MAPKs in UA-induced tubular cell apoptosis (29,30). As the underlying mechanisms required further elucidation, the present study examined the phosphorylation of P38 and ERK1/2 and found them significantly activated following exposure to UA.…”
Section: Discussionmentioning
confidence: 94%
“…131 Src family kinase was also activated in HK-2 cells following stimulation with Ox-HDL, and apoptosis was increased. 131…”
Section: [H2] Interactions With Oxidized Lipidsmentioning
confidence: 97%
“…126 In human renal tubular (HK-2) and mesangial cells, binding of Ox-HDL to CD36 enhanced ROS production and upregulated the expression of proinflammatory factors via activation of p38/MAPK, extracellular-regulated kinase (ERK)/MAPK and NF-κB. 131 Src family kinase was also activated in HK-2 cells following stimulation with Ox-HDL, and apoptosis was increased. 131…”
Section: [H2] Interactions With Oxidized Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that proteinuria results in accumulation of cholesterol in the kidney and that this is associated with upregulation of CD36, but also SRA-1 and ACAT1 and activation of SREBP-2 which can collectively raise tissue cholesterol and promote renal injury by facilitating the influx, synthesis and retention of cholesterol in the nephrotic kidney (18). The findings of a recent study suggest that oxidized HDL enhances the pro-inflammatory properties and impairs the function of Human renal proximal tubule epithelial cells which play an important role in the progression of CKD, mainly through the scavenger receptor, CD36, as well as through the Src, MAPK and NF-κB pathways (19). Finally, Kennedy et al…”
Section: Discussionmentioning
confidence: 99%